Titanium suboxide ceramic and preparation method and application thereof

CN120736892BActive Publication Date: 2026-10-30SHANGHAI JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510952824.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-10
Publication Date
2026-10-30
Estimated Expiration
2045-07-10

AI Technical Summary

Technical Problem

[0003]本发明所解决的技术问题在于克服现有技术中存在的亚氧化钛制备工艺苛刻及亚氧化钛陶瓷的力学性能差的缺陷,提供一种亚氧化钛陶瓷及其制备方法、应用

Benefits of technology

[0029]本发明所提供的亚氧化钛陶瓷对制备工艺的要求低且制备方法简单,所制备的亚氧化钛陶瓷具有优异的力学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120736892B_ABST
    Figure CN120736892B_ABST
Patent Text Reader

Abstract

The application discloses a titanium suboxide ceramic and a preparation method and application thereof. The preparation method comprises the following steps: sintering a mixture of TiO and Ti into a shape or first shaping and then sintering, so as to obtain the titanium suboxide ceramic TiO x , wherein 0 < x < 1. The titanium suboxide ceramic provided by the application has low requirements on a preparation process and a simple preparation method, and the prepared titanium suboxide ceramic has excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention specifically relates to a titanium suboxide ceramic, its preparation method, and its application. Background Technology

[0002] Titanium oxide ceramics, as an important branch of metal oxide ceramic systems, possess unique physicochemical properties that give them irreplaceable advantages in multiple fields, making them a crucial supplement and upgrade direction for traditional oxide ceramics. Especially in high-end fields such as aerospace and energy devices, where extremely high performance requirements for structural materials are placed, the development of novel ceramic materials with both excellent mechanical strength and toughness is crucial for overcoming bottlenecks in their engineering applications. Traditional titanium dioxide (TiO2) ceramics suffer from high mechanical brittleness (fracture toughness of only 2–3 MPa·m). 1 / 2 However, due to its inherent limitations such as low photocatalytic efficiency and insufficient high-temperature stability, it is difficult to meet the requirements of extreme environment applications. Sub-titanium oxide ceramics, on the other hand, utilize a metallic bond network formed by low-valence titanium (accounting for 30%) and oxygen vacancies (density 1.2 × 10⁻⁶). 20 cm -3 The synergistic mechanism of ) breaks through the performance bottleneck of traditional oxides, and its fracture toughness (5.6MPa·m) 1 / 2 The compressive strength (1.2 GPa) is increased by 100% and 40% compared to TiO2, respectively, and it also has the characteristics of thermal shock resistance (performance retention rate ≥85% from -196℃ to 1200℃) and radiation resistance (corrosion rate 0.001 mm / year). However, the current titanium suboxide preparation process still faces problems such as difficulty in controlling the reduction process and insufficient grain boundary stability, which can affect the density and homogenization of titanium suboxide ceramics, making it difficult to sinter and form the ceramics or resulting in porosity and cracks, thus affecting its hardness and toughness. Summary of the Invention

[0003] The technical problem solved by this invention is to overcome the shortcomings of existing technologies, such as the demanding preparation process of titanium suboxide and the poor mechanical properties of titanium suboxide ceramics, and to provide a titanium suboxide ceramic, its preparation method, and its applications. The titanium suboxide ceramic provided by this invention has low requirements for the preparation process and a simple preparation method, and the prepared titanium suboxide ceramic exhibits excellent mechanical properties.

[0004] The present invention solves the above-mentioned technical problems through the following technical solutions:

[0005] This invention provides a method for preparing titanium suboxide ceramics, comprising the following steps: sintering a mixture of TiO and Ti into shape, or shaping first and then sintering, to obtain the titanium suboxide ceramic TiO. x , where 0 < x < 1.

[0006] In this invention, the TiO can be prepared by conventional methods in the art or purchased commercially. The preparation method of the TiO preferably includes the following steps: calcining and acid washing a mixture of TiO2 and Mg sequentially.

[0007] The TiO2 particle size can be 10-200 nm, preferably 10-100 nm, such as 20 nm, 40 nm, 60 nm or 80 nm. The Mg particle size can be 50-500 mesh, such as 100-200 mesh. The molar ratio of TiO2 to Mg can be conventional in the art, generally 1:1.

[0008] The preferred method for preparing the mixture of TiO2 and Mg includes the following steps: grinding TiO2 and Mg. The grinding is generally carried out in a mortar. The grinding time can be 10-60 minutes, for example, 30 minutes or 40 minutes.

[0009] The calcination is generally carried out in a tube furnace. The calcination atmosphere is generally an inert atmosphere, such as argon or nitrogen. The calcination temperature can be 700-1200℃, for example 900℃, 1000℃ or 1100℃. The calcination time can be 6-24h, for example 10h or 12h.

[0010] The acid used in the pickling process can be any conventional acid in the art, generally hydrochloric acid, sulfuric acid, or nitric acid, such as dilute hydrochloric acid obtained by mixing concentrated hydrochloric acid and deionized water at a volume ratio of 1:6. During the pickling process, the mass ratio of the solid powder to the acid volume can be 1:(3-10) g / mL, for example, 1:7 g / mL. The pickling is preferably carried out under stirring. The pickling time can be 20-60 min, for example, 25 min, 30 min, or 40 min. The number of pickling cycles can be conventional in the art, generally three times. After the pickling, washing, drying, and grinding are generally required. The washing can generally use deionized water and / or ethanol.

[0011] In this invention, the molar ratio of TiO to Ti can be x:(1-x), where 0 < x < 1. For example, x can be 0.02, 0.05, 0.08, 0.09, 0.1, 0.12, 0.15, 0.18, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.6, 0.72, 0.75, 0.8, 0.82, or 0.9. Preferably, 0.02 < x ≤ 0.08 or 0.12 < x ≤ 0.6. Here, x is the same as that of the titanium suboxide ceramic TiO. x x in the text.

[0012] In this invention, the particle size of Ti can be 50-500 mesh, for example 100 mesh, 200 mesh, 325 mesh or 400 mesh.

[0013] In this invention, the preparation method of the mixture of TiO and Ti preferably includes the following steps: grinding TiO powder and Ti powder evenly. The grinding is generally carried out in a mortar. The grinding time can be 10-30 minutes, for example, 20 minutes.

[0014] In this invention, the sintering process is preferably performed using spark plasma sintering. The sintering process is preferably carried out in a spark plasma furnace. The sintering process is generally performed under vacuum or in an inert atmosphere. The rate of heating to the sintering temperature can be 40-110°C / min, for example, 50°C / min, 80°C / min, or 100°C / min. The sintering temperature can be 1000-1800°C, for example, 1250°C, 1300°C, or 1500°C. The sintering time can be 10-360 min, for example, 15 min, 20 min, 30 min, 50 min, 100 min, 180 min, or 250 min.

[0015] When the spark plasma sintering method is used, the pressure during the sintering process can be 15-50 MPa, for example 20 MPa, 30 MPa, 35 MPa or 40 MPa.

[0016] In some preferred embodiments, the sintering process includes the following steps: heating the mixture of TiO and Ti to 1300°C at a rate of 100°C / min, then continuing to heat it to 1500°C at a rate of 50°C / min and holding it at that temperature for 10-360 min.

[0017] In some preferred embodiments, the sintering process includes the following steps: heating the mixture of TiO and Ti to 1300°C at a rate of 100°C / min under a pressure of 30 MPa, and then continuing to heat it to 1500°C at a rate of 50°C / min and holding it at that temperature for 10-360 min.

[0018] In this invention, when the method of first forming and then sintering is adopted: the forming method and the equipment used can be conventional in the art, such as tableting in a tablet press; the equipment used for sintering can be conventional in the art, such as in a tube furnace or a spark plasma furnace; the sintering is generally carried out in a vacuum or in an inert atmosphere; the rate of heating to the sintering temperature can be 40-110℃ / min, for example 50℃ / min, 80℃ / min or 100℃ / min; the sintering temperature can be 1000-1800℃, for example 1200℃, 1300℃, 1500℃ or 1550℃; the sintering time can be 10min-5h, for example 15min, 30min, 1h, 2h or 4.5h.

[0019] In this invention, in order to further improve the density of the sub-titanium oxide ceramic, it is preferable to subject the sub-titanium oxide ceramic to annealing treatment.

[0020] The annealing process is typically performed in a vacuum furnace. During the annealing process, the oxygen partial pressure can be 10. -1 -10 -6 Pa, for example, is 10 -5 Pa. The annealing temperature can be 800-1200℃, for example 900℃, 1000℃ or 1100℃. The annealing time can be 24-100h, for example 48h, 72h or 84h.

[0021] In this invention, the sub-titanium oxide ceramic TiO x In this context, x is, for example, 0.02, 0.05, 0.08, 0.09, 0.1, 0.12, 0.15, 0.18, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.6, 0.72, 0.75, 0.8, 0.82, or 0.9, preferably 0.02 < x ≤ 0.08 or 0.12 < x ≤ 0.6.

[0022] In this invention, the shape of the sub-titanium oxide ceramic can be conventional in the art, such as sheet or block.

[0023] The present invention also provides a titanium suboxide ceramic prepared by the preparation method described above.

[0024] In this invention, the Vickers hardness of the titanium suboxide ceramic can be 400-800 HV, for example 450 HV, 500 HV, 559.04 HV, 600 HV, 650 HV, 671.09 HV, 700 HV, or 751.97 HV, preferably 450-800 HV. The elastic modulus of the titanium suboxide ceramic can be 130-400 GPa, for example 137.3 GPa, 150 GPa, 187.9 GPa, 200 GPa, 250 GPa, or 288.9 GPa. The nanoindentation hardness of the titanium suboxide ceramic can be 7.5-14 GPa, for example 8 GPa, 8.37 GPa, 9 GPa, 9.5 GPa, 10.21 GPa, 11 GPa, or 12.78 GPa.

[0025] The present invention also provides an application of the aforementioned titanium suboxide ceramic in aerospace materials, hydrogen storage containers, energy devices, extreme environment chemical engineering equipment, or biomedical materials.

[0026] Based on common knowledge in the field, the above-mentioned preferred conditions can be combined arbitrarily to obtain various preferred embodiments of the present invention.

[0027] The reagents and raw materials used in this invention are all commercially available.

[0028] The positive and progressive effects of this invention are as follows:

[0029] The titanium suboxide ceramic provided by this invention has low requirements for the preparation process and the preparation method is simple. The prepared titanium suboxide ceramic has excellent mechanical properties. Attached Figure Description

[0030] Figure 1 SEM image of TiO powder prepared in Example 1;

[0031] Figure 2 The image shows the XRD pattern of the TiO powder prepared in Example 1.

[0032] Figure 3 TiO2 prepared in Example 2 0.05 SEM image of the ceramic block;

[0033] Figure 4 TiO2 prepared in Example 7 0.05 SEM image of the ceramic block. Detailed Implementation

[0034] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions.

[0035] Example 1

[0036] Preparation of TiO powder: Nano-TiO2 (99.8%, 60nm, Aladin) and Mg (≥99.0%, 100-200 mesh, Sinopharm) with a molar ratio of 1:1 were mixed in a quartz mortar and ground for 30 min to ensure uniform mixing. 10g of the mixed powder was added to an alumina ceramic boat and placed in a tube furnace. Argon gas was passed through the tube at a flow rate of 200mL / min for 30 min to purge the atmosphere. Then, under the same argon flow rate, the temperature was increased to 1000℃ at a rate of 5℃ / min and maintained at this temperature for 10 h. The furnace was then cooled to room temperature. The flaky sample was removed and ground into powder in a quartz mortar. 30mL of concentrated hydrochloric acid and 180mL of deionized water were mixed and stirred until homogeneous to obtain dilute hydrochloric acid. 70mL of dilute hydrochloric acid was added to the Mg-reduced TiO2 powder in a beaker and stirred at a rate of 400r / min for 30 min. After standing for 5 min, the mixture was filtered. Another 70mL of dilute hydrochloric acid was added to the filter residue, and this process was repeated three times to remove MgO. The filter residue was washed three times with deionized water and anhydrous ethanol, and then dried and ground to obtain TiO powder.

[0037] Example 2

[0038] TiO 0.05 Ceramic bulk sintering: TiO powder and Ti (99.5%, 325 mesh, Innochem) with a molar ratio of 0.05:0.95 were mixed in a quartz mortar and ground for 20 minutes to ensure homogeneity. TiO was then prepared by spark plasma sintering (SPS) experiments using a mini SPS spark plasma furnace (SPS-3T-5-MIN, Shanghai Chenhua Technology Co., Ltd.). 0.05 Ceramic bulk. 3.0 g of the mixed powder was loaded into a graphite mold with an inner diameter of 12 mm. The powder sample was separated from the graphite mold and punch using 0.1 mm graphite paper. The mixed ceramic was heated to 1300 °C in a vacuum (≤10 Pa) at a rate of 100 °C / min under a uniaxial pressure of 30 MPa, and then further heated to 1500 °C at a rate of 50 °C / min. The sample was held at this temperature and pressure for 15 min and then allowed to cool naturally to room temperature to prepare TiO2. 0.05 Ceramic block. To minimize heat radiation, the mold is wrapped with graphite wool. The surface graphite is removed by grinding, and the block is kept in a cylindrical shape with a diameter of 11 mm and a thickness of 5 mm. One bottom surface is polished using a polishing machine.

[0039] Example 3

[0040] TiO 0.15Ceramic bulk sintering: TiO powder and Ti (99.5%, 325 mesh, Innochem) with a molar ratio of 0.15:0.85 were mixed in a quartz mortar and ground for 20 minutes to ensure homogeneity. TiO was then prepared by spark plasma sintering (SPS) experiments using a mini SPS spark plasma furnace (SPS-3T-5-MIN, Shanghai Chenhua Technology Co., Ltd.). 0.15 Ceramic bulk. 3.0 g of the mixed powder was loaded into a graphite mold with an inner diameter of 12 mm. The powder sample was separated from the graphite mold and punch using 0.1 mm graphite paper. The mixed ceramic was heated to 1300 °C in a vacuum (≤10 Pa) at a rate of 100 °C / min under a uniaxial pressure of 30 MPa, and then further heated to 1500 °C at a rate of 50 °C / min. The sample was held at this temperature and pressure for 30 min and then allowed to cool naturally to room temperature to prepare TiO2. 0.15 Ceramic block. To minimize heat radiation, the mold is wrapped with graphite wool. The surface graphite is removed by grinding, and the block is kept in a cylindrical shape with a diameter of 11 mm and a thickness of 5 mm. One bottom surface is polished using a polishing machine.

[0041] Example 4

[0042] TiO 0.45 Ceramic bulk sintering: TiO powder and Ti (99.5%, 325 mesh, Innochem) with a molar ratio of 0.45:0.55 were mixed in a quartz mortar and ground for 20 minutes to ensure homogeneity. TiO was then prepared by spark plasma sintering (SPS) experiments using a mini SPS spark plasma furnace (SPS-3T-5-MIN, Shanghai Chenhua Technology Co., Ltd.). 0.45 Ceramic bulk. 3.0 g of the mixed powder was loaded into a graphite mold with an inner diameter of 12 mm. The powder sample was separated from the graphite mold and punch using 0.1 mm graphite paper. The mixed ceramic was heated to 1300 °C in a vacuum (≤10 Pa) at a rate of 100 °C / min under a uniaxial pressure of 30 MPa, and then further heated to 1500 °C at a rate of 50 °C / min. The sample was held at this temperature and pressure for 180 min and then allowed to cool naturally to room temperature to prepare TiO2. 0.45 Ceramic block. To minimize heat radiation, the mold is wrapped with graphite wool. The surface graphite is removed by grinding, and the block is kept in a cylindrical shape with a diameter of 11 mm and a thickness of 5 mm. One bottom surface is polished using a polishing machine.

[0043] Example 5

[0044] Compared with Example 2, except that the molar ratio of TiO powder to Ti was adjusted to 0.2:0.8, all other operations and conditions were the same as in Example 2, and TiO was obtained. 0.2Ceramic blocks.

[0045] Example 6

[0046] Compared with Example 2, except that the molar ratio of TiO powder to Ti was adjusted to 0.35:0.65, all other operations and conditions were the same as in Example 2, and TiO was obtained. 0.35 Ceramic blocks.

[0047] Example 7

[0048] The TiO2 prepared in Example 2 0.05 The ceramic block undergoes annealing treatment: the temperature is raised to 1000℃ in a vacuum furnace at a heating rate of 5℃ / min, held for 72 hours, and the oxygen partial pressure is controlled at 10. -5 Pa, cooled to room temperature with the furnace.

[0049] Comparative Example 1

[0050] Ti metal bulk sintering: Ti metal bulks were prepared using a mini SPS spark plasma sintering (SPS) furnace (SPS-3T-5-MIN, Shanghai Chenhua Technology Co., Ltd.). 3.0 g of Ti powder was placed into a graphite mold with an inner diameter of 12 mm. The powder sample was separated from the graphite mold and punch using 0.1 mm graphite paper. Under a uniaxial pressure of 30 MPa, the mixed ceramic was heated to 1300 °C at a rate of 100 °C / min in a vacuum (≤10 Pa), and then to 1500 °C at a rate of 50 °C / min. The sample was held at this temperature and pressure for 15 min and then allowed to cool naturally to room temperature to prepare the Ti metal bulk. To minimize heat radiation, the mold was wrapped with graphite wool. Surface graphite was removed by grinding, maintaining the bulk size as a cylindrical block with a diameter of 11 mm and a thickness of 5 mm. One bottom surface was polished using a polishing machine.

[0051] Effect Example

[0052] (1) Morphological characterization and XRD testing

[0053] According to SEM ( Figure 1 ) and XRD Figure 2 As can be seen, TiO powder was successfully prepared in Example 1. According to the crystal data in Table 1, the TiO powder prepared in Example 1 belongs to the monoclinic crystal system with space group A2 / m.

[0054] Table 1. Crystal data of TiO powder prepared in Example 1

[0055]

[0056]

[0057] according to Figure 3 and Figure 4 It is evident that the SPS sintered sample surface, due to the grinding process before mechanical testing, exhibits dense, parallel linear scratches with a width of approximately 1-3 μm. Some scratch edges are accompanied by micro-cracks formed by grain peeling, and the surface grain orientation is disordered, with microcracks present. However, after vacuum annealing, the scratches on the sample surface are significantly reduced, leaving only very shallow trace outlines, and the overall surface exhibits a smooth and dense characteristic. The grain boundary clarity is improved, and the size increases from approximately 2-5 μm to 3-6 μm, reflecting that atomic diffusion fills the scratch pits and repairs lattice distortion during the annealing process. Annealing promotes thermally activated atomic diffusion, which on the one hand repairs the submicron-level surface defect network caused by grinding and reduces stress concentration, and on the other hand promotes dislocation rearrangement to eliminate grinding-induced residual stress (from ~200 MPa to ~50 MPa) and optimize the grain boundary structure (grain boundary energy is reduced by approximately 30%), thus providing a structurally stable sample basis for mechanical testing.

[0058] (2) Vickers hardness test

[0059] Using a Vickers hardness tester (HMV-G21D), the test load was set to HV0.5 (4.903N) and the holding time was 15s. The Vickers hardness was tested on the polished surface of the sample. Each sample was tested four times and the average value was taken.

[0060] The Vickers hardness test results are shown in Table 2:

[0061] Table 2 Vickers Hardness Test Results

[0062]

[0063] (3) Nanoindentation hardness and elastic modulus testing

[0064] Using an in-situ nanomechanical testing instrument (G200), with the Poisson's ratio of the sample set to 0.3, the nanoindentation hardness and elastic modulus were tested on the polished surface of the sample within a continuous depth range of 600-900 nm in the thickness direction. Each sample was tested five times and the average value was taken.

[0065] Table 3. Results of Nanoindentation Hardness and Elastic Modulus Tests

[0066]

[0067] (4) Young's modulus test

[0068] The Young's modulus of the material was tested using a universal testing machine, and the test results are shown in Table 4.

[0069] Table 4

[0070]

[0071] As shown in Table 4, the oxygen content has a nonlinear effect on the mechanical properties of titanium-based materials, which is "first strengthened and then weakened": low oxygen (0.05) significantly increases the Young's modulus to 332.57 GPa through solid solution strengthening; medium oxygen (0.2) causes the modulus to drop to 254.12 GPa due to solid solution saturation or the emergence of a second phase; and high oxygen (0.35) has a modulus close to that of pure titanium (119.17 GPa) due to the dominance of the brittle phase.

[0072] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely illustrative examples, and the scope of protection of the present invention is defined by the appended claims. Those skilled in the art can make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but all such changes and modifications fall within the scope of protection of the present invention.

Claims

1. A method for preparing sub-titanium oxide ceramic, characterized in that, The process includes the following steps: calcining and acid washing a mixture of TiO2 and Mg sequentially to obtain TiO; sintering the mixture of TiO and Ti into a shape, or shaping first and then sintering, to obtain the sub-titanium oxide ceramic TiO. x where 0 < x < 1; The molar ratio of TiO to Ti is y:(1-y), where 0.02≤y≤0.3 or 0.4≤y≤0.6; During the sintering process, the rate of heating to the sintering temperature is 40-110℃ / min, the sintering temperature is 1000-1800℃, and the sintering time is 10-360min. In the process of first forming and then sintering, the rate of heating to the sintering temperature is 40-110℃ / min, the sintering temperature is 1000-1800℃, and the sintering time is 10min-5h.

2. The method for preparing sub-titanium oxide ceramic as described in claim 1, characterized in that, The molar ratio of TiO to Ti is y:(1-y), where y is 0.02, 0.05, 0.08, 0.09, 0.1, 0.12, 0.15, 0.18, 0.2, 0.25, 0.3, 0.4, 0.45, 0.5, or 0.6; And / or, the particle size of the Ti is 50-500 mesh.

3. The method for preparing sub-titanium oxide ceramic as described in claim 2, characterized in that, The Ti has a particle size of 100 mesh, 200 mesh, 325 mesh or 400 mesh.

4. The method for preparing sub-titanium oxide ceramic as described in claim 1 or 2, characterized in that, The sintering process satisfies one or more of the following conditions: (1) The sintering process is carried out by spark plasma sintering. (2) The sintering temperature is 1250℃, 1300℃ or 1500℃; (3) The sintering time is 15 min, 20 min, 30 min, 50 min, 100 min, 180 min or 250 min.

5. The method for preparing sub-titanium oxide ceramic as described in claim 4, characterized in that, When the spark plasma sintering method is used, the pressure during the sintering process is 15-50 MPa.

6. The method for preparing sub-titanium oxide ceramic as described in claim 5, characterized in that, When the spark plasma sintering method is used, the pressure during the sintering process is 20 MPa, 30 MPa, 35 MPa or 40 MPa.

7. The method for preparing sub-titanium oxide ceramic as described in claim 1 or 2, characterized in that, The sintering process includes the following steps: heating the mixture of TiO and Ti to 1300°C at a rate of 100°C / min, then continuing to heat it to 1500°C at a rate of 50°C / min and holding it at that temperature for 10-360 min.

8. The method for preparing sub-titanium oxide ceramic as described in claim 7, characterized in that, The sintering process includes the following steps: under a pressure of 30 MPa, the mixture of TiO and Ti is first heated to 1300°C at a rate of 100°C / min, and then heated to 1500°C at a rate of 50°C / min and held at that temperature for 10-360 min.

9. The method for preparing sub-titanium oxide ceramic as described in claim 1 or 2, characterized in that, When the above-mentioned method of first forming and then sintering is adopted, the sintering temperature is 1200℃, 1300℃, 1500℃ or 1550℃; And / or, when the method of first forming and then sintering is adopted, the sintering time is 15 min, 30 min, 1 h, 2 h or 4.5 h.

10. The method for preparing sub-titanium oxide ceramic as described in claim 1 or 2, characterized in that, The sub-titanium oxide ceramic as described in claim 1 is subjected to annealing treatment.

11. The method for preparing sub-titanium oxide ceramic as described in claim 10, characterized in that, The annealing temperature is 800-1200℃.

12. The method for preparing sub-titanium oxide ceramic as described in claim 11, characterized in that, The annealing temperature is 900℃, 1000℃ or 1100℃.

13. The method for preparing sub-titanium oxide ceramic as described in claim 10, characterized in that, The annealing process takes 24-100 hours.

14. The method for preparing sub-titanium oxide ceramic as described in claim 13, characterized in that, The annealing process takes 48 hours, 72 hours, or 84 hours.

15. The method for preparing sub-titanium oxide ceramic as described in claim 1 or 2, characterized in that, The titanium suboxide ceramic TiO x In the given values, x is 0.02, 0.05, 0.08, 0.09, 0.1, 0.12, 0.15, 0.18, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.6, 0.72, 0.75, 0.8, 0.82, or 0.

9.

16. The method for preparing sub-titanium oxide ceramic as described in claim 1 or 2, characterized in that, The titanium suboxide ceramic TiO x In the case of 0.02 < x ≤ 0.08 or 0.12 < x ≤ 0.

6.

17. The method for preparing sub-titanium oxide ceramic as described in claim 1 or 2, characterized in that, The calcination temperature is 700-1200℃; And / or, the calcination time is 6-24 hours.

18. The method for preparing sub-titanium oxide ceramic as described in claim 17, characterized in that, The calcination temperature is 900℃, 1000℃ or 1100℃.

19. The method for preparing sub-titanium oxide ceramic as described in claim 17, characterized in that, The calcination time is 10 hours or 12 hours.

20. A titanium suboxide ceramic prepared by the method described in any one of claims 1-19.

21. The application of the sub-titanium oxide ceramic as described in claim 20 in aerospace materials, hydrogen storage containers, energy devices, extreme environment chemical engineering equipment, or biomedical materials.

Citation Information

Patent Citations

  • Ti-O electronic compound, lithium-sulfur battery electrode material, preparation method and application of Ti-O electronic compound and lithium-sulfur battery electrode material

    CN120247549A

  • MANUFACTURING METHOD OF MgO-TiO-BASED SPUTTERING TARGET

    JP2020147822A